DIGITIZATION OF PUBLIC SERVICES AS A DEVELOPMENT STRATEGY VILLAGE E-GOVERNMENT - Lestari, Chantika Cindy; Agustina, Isna Fitria (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This research aims to understand the implementation of E-Government in Bleberan Village, focusing on three main aspects: support, capacity, and benefits. Digitization of public services at the village level is important because villages are at the forefront of providing services to the community, but often face limited resources. Method: This study uses a descriptive qualitative approach with case studies, through interviews with village officials and direct observation of existing digital service processes. Results: The results of the study show that the implementation of E-Government in Bleberan Village is still highly dependent on applications provided by the local government, such as Siskeudes and Paradewi. The main obstacles arise from the limited capacity of village apparatus which is mostly not technologically advanced, lack of training, and unstable internet networks. However, digital applications have been proven to help the efficiency of financial management and population administration services. People are also starting to feel the benefits, especially the younger generation who use simple channels such as WhatsApp to take care of documents. Novelty: The novelty of this study lies in a realistic picture of the dynamics of the implementation of E-Government in remote villages. These findings show that the success of digitalization at the village level is highly dependent on the internal readiness of the village, the support of local governments, and the continuous improvement of people's digital literacy.